2015
DOI: 10.2147/mder.s57252
|View full text |Cite
|
Sign up to set email alerts
|

Special considerations for placement of an inflatable penile prosthesis for the patient with Peyronie's disease: techniques and patient preference

Abstract: Placement of an inflatable penile prosthesis (IPP) is the mainstay of surgical treatment for patients with Peyronie’s disease (PD) and concomitant medication-refractory erectile dysfunction. Special considerations and adjunctive surgical techniques during the IPP procedure are often required for patients with PD to improve residual penile curvature, as well as postoperative penile length. The surgical outcomes and various adjunctive techniques are not significantly different from one another, and selection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…When IPP insertion alone does not sufficiently correct penile curvature, manual modeling is the next step to reduce residual curvature ( 1 , 7 , 17 , 19 , 20 , 62 , 63 ). Most studies have shown that between 10% and 61% of patients with PD may need additional straightening procedures after simple IPP implantation ( 6 , 17 - 19 , 26 , 53 , 54 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When IPP insertion alone does not sufficiently correct penile curvature, manual modeling is the next step to reduce residual curvature ( 1 , 7 , 17 , 19 , 20 , 62 , 63 ). Most studies have shown that between 10% and 61% of patients with PD may need additional straightening procedures after simple IPP implantation ( 6 , 17 - 19 , 26 , 53 , 54 ).…”
Section: Methodsmentioning
confidence: 99%
“…While modeling is highly successful in adjusting residual curvature after IPP insertion, many authors have reported significant residual curvature in 20–30% of patients that required additional surgery ( 68 ). When post-modeling residual curvature exceeds 30°, most algorithms recommend a plaque-releasing incision or plication to further reduce the curvature ( 1 , 7 , 19 , 20 , 62 , 69 , 70 ). A releasing incision is a lengthening procedure, such that a dissection made in the fibrotic plaque of the tunica albuginea overlying the area of maximum curvature lengthens the concave side of the penis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation